Dictionary of food ingredients - Igoe, Robert S. (Springer, 2011)
Dictionary of Food Ingredients is a concise, easy-to-use resource covering over 1,000 food ingredients and additives, including natural ingredients, FDA-approved artificial ingredients, and compounds used in food processing. Organized alphabetically, definitions cover functionality, chemical properties, and applications, and thorough cross-referencing allows readers to follow related and similar ingredients. A section based on the Code of Federal Regulations lists food ingredients according to their US approval status, and a bibliography pinpoints further information. This revised and updated fifth edition features a new section, ?Food Definitions and Formulations,? and a thoroughly expanded list of food ingredients approved for use in the European Union, with E numbers. In addition, the fifth edition provides new information on existing and more recently approved ingredients. The Dictionary is an unparalleled source of information, providing practical, scientific, and regulatory information on every important ingredient and category. This resource will be of value to food scientists, ingredient suppliers, dietitians, extension specialists, food customer service personnel, and students.